Intramolecular donor-stabilized tetra-coordinated germanium(iv) di-cations and their Lewis acidic properties - Peddi, Balakrishna; Khan, Souvik; Gonnade, Rajesh G.; Yildiz, Cem B.; Majumdar, Moumita (Chemical Science, 2023)
We report the first examples of intramolecular phosphine-stabilized tetra-coordinated germanium(iv) di-cationic compounds: [(L2Ge)-Ge-iPr][CF3SO3](2)3iPr and [(L2Ge)-Ge-Ph][CF3SO3](2)3Ph (L-iPr = 6-(diisopropylphosphanyl)-1,2-dihydroacenaphthylene-5-ide; L-Ph = 6-(diphenylphosphanyl)-1,2-dihydroacenaphthylene-5-ide). The step wise synthetic strategy involves the isolation of neutral and mono-cationic Ge(iv) precursors: [(L2GeCl)-Ge-iPr][X] (X = GeCl(3)1iPr, OTf 2iPr), [(L2GeCl2)-Ge-Ph] 1Ph and [(L2GeCl)-Ge-Ph][OTf] 2Ph. Both 3iPr and 3Ph exhibit constrained spiro-geometry. DFT studies reveal the dispersion of di-cationic charges over P-Ge-P sites. Anion or Lewis base binding occurs at the Ge site resulting in relaxed distorted trigonal bipyramidal/tetrahedral geometry. 3iPr and 3Ph activate the Si-H bond initially at the P-site. The hydride ultimately migrates to the Ge-site rapidly giving [(L2GeH)-Ge-Ph][CF3SO3] 3PhH, while sluggishly forming [(L2GeH)-Ge-iPr][CF3SO3] 3iPrH. Compounds 3iPr and 3Ph were tested as catalysts for the hydrosilylation of aromatic aldehydes. While catalytic hydrosilylation proceeded via the initial Et3Si-H bond activation in the case of 3iPr, compound 3Ph as a catalyst showed a masked Frustrated Lewis Pair (FLP) type reactivity in the catalytic cycle.